Adenosine signalling in T-cell activation favours development of IL-17 positive cells with suppressive properties - Leikeim, Lisa; Li, Hui; An, Liying; Sticht, Carsten; Krämer, Bernhard; Yard, Benito A.; Leipe, Jan; Kälsch, Anna-Isabelle (Immunology, 2023)
Evidence suggests that the anti-inflammatory nucleoside adenosine can shape immune responses by shifting the regulatory (Treg)/helper (Th17) T-cell balance in favour of Treg. Since this observation is based on in vivo and in vitro studies mostly confined to murine models, we comprehensively analysed effects of adenosine on human T-cells. Proliferation, phenotype and cytokine production of stimulated T-cells were assessed by flow cytometry, multiplex assay and ELISA, gene expression profiling was determined by microarray. We found that the pan-adenosine agonist 5′-N-ethylcarboxamidoadenosine (NECA) skews human CD3+ T-cell responses towards non-inflammatory Th17 cells. Addition of NECA during T-cell activation increased the development of IL-17+ cells with a CD4+ RORγt+ phenotype and enhanced CD161 and CD196 surface expression. Remarkably, these Th17 cells displayed non-inflammatory cytokine and gene expression profiles including reduced Th1/Th17 transdifferentiation, a stem cell-like molecular signature and induced surface expression of the adenosine-producing ectoenzymes CD39 and CD73. Thus, T-cells cultured under Th17-inducing conditions together with NECA were capable of suppressing responder T-cells. Finally, genome-wide gene expression profiling revealed metabolic quiescence previously associated with non-pathogenic Th17 cells in response to adenosine signalling. Our data suggest that adenosine induces non-inflammatory Th17 cells in human T-cell differentiation, potentially through regulation of metabolic pathways.